THE IMPACT OF EMOTIONAL INTELLIGENCE ON JOB OUTCOMES AND ITS IMPACT TO TURNOVER INTENTION - HAKIM, WIDYATAMA LUKMAN NUR; ANGGRAENI, ADE IRMA (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
This research is a human resource analysis study, especially studies on employees of Warung SS Purwokerto. The purpose of this study is to analyze the impact of Emotional Intelligence on Job Outcomes and its impact to Turnover Intention on Warung SS Purwokerto. The samples in this study were 86 people who had been selected using purposive sampling. This study uses the analysis method of Simple Regression Analysis and Causal Step Method. Hypotheses indicate that emotional intelligence directly affects job satisfaction, organizational commitment and Turnover Intention, then job satisfaction and organizational commitment affects Turnover Intention, next  job satisfaction and organizational commitment affect the effect of emotional intelligence on Turnover Intention. The implications of this study indicate that Turnover Intention affected by emotional intelligence, job satisfaction and organizational commitment. This finding will contribute to future research as an additional reference regarding the development of discussions and studies on human resource management.